Post traumatic cutaneous-biliary- renal fistula. - Pressa, Carlos; Croci, Fabio; dos Santos, Gustavo; Maquieira, Gonzalo; García Ruiz, Susana (Cirugía del Uruguay, 1985)
Authors present a case of a fistula occurring as a consequence of shot in the stomach at the leve! of the right hypochondrium, with liver and renal lesion. Authors discuss its pathogenia and related therapeutic aspects. Stress is laid on the exceptional character of same.